2023
DOI: 10.3389/fcvm.2023.1124106
|View full text |Cite
|
Sign up to set email alerts
|

Periadventitial β-aminopropionitrile-loaded nanofibers reduce fibrosis and improve arteriovenous fistula remodeling in rats

Abstract: BackgroundArteriovenous fistula (AVF) postoperative stenosis is a persistent healthcare problem for hemodialysis patients. We have previously demonstrated that fibrotic remodeling contributes to AVF non-maturation and lysyl oxidase (LOX) is upregulated in failed AVFs compared to matured. Herein, we developed a nanofiber scaffold for the periadventitial delivery of β-aminopropionitrile (BAPN) to determine whether unidirectional periadventitial LOX inhibition is a suitable strategy to promote adaptive AVF remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Both treatments decreased fibrosis and shear stress and improved flow volume and distensibility in the AVF. A follow-up rat study showed that a BAPN-loaded PGLA nanofibre scaffold around the AVF promotes OR, prevents adventitial fibrosis, and improves vascular compliance [ 109 ]. BAPN and LOX, however, are both involved in cross-linking of collagen as well as elastin fibres and are, therefore, not exclusively related to collagen [ 110 ].…”
Section: Rebuilding the Vascular Framework: Ecm Remodelling During Av...mentioning
confidence: 99%
“…Both treatments decreased fibrosis and shear stress and improved flow volume and distensibility in the AVF. A follow-up rat study showed that a BAPN-loaded PGLA nanofibre scaffold around the AVF promotes OR, prevents adventitial fibrosis, and improves vascular compliance [ 109 ]. BAPN and LOX, however, are both involved in cross-linking of collagen as well as elastin fibres and are, therefore, not exclusively related to collagen [ 110 ].…”
Section: Rebuilding the Vascular Framework: Ecm Remodelling During Av...mentioning
confidence: 99%
“…Therefore, fibrotic remodeling and NIH, which in combination significantly increase the risk of AVF failure ( 14 ). Our previous study have shown that in the inferior vena cava of adenine-induced chronic kidney disease rats with aortocaval fistulas, in addition to the disordered EC and SMC, inflammatory cells such as macrophage (Mφ) are also present in the major cellular components of NIH ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…AVF fibrosis can be attributed to excessive extracellular matrix (ECM) synthesis by activated VSMAs and myofibroblasts and/or insufficient ECM degradation by matrix metalloproteinases (MMP). Excessive fibrosis may reduce vessel wall compliance, and AVF patients with intermediate fibrosis have less increase in venous diameter during reconstruction (13). When the vessel wall loses compliance due to excessive ECM deposition, the NIH becomes obstructive (possibly less compressible under high blood flow) and stenotic.…”
Section: Introductionmentioning
confidence: 99%